THE INFLUENCE OF CASH FLOW STATEMENT TO STOCK PRICES AND STOCK RETURNS ( Studies for Non-Financial Sectors Companies In Jakarta Stock Exchage ) - Eka Nurmala Sari (Jurnal Riset AKuntansi dan Bisnis, 2007)
The objective of this research is to analyze simultaneously and partially the influence of cash flow statement that involves cash flow of operating, cash flow of investing, and cash flow of financing, to stock prices and stock returns. The number of samples are 70 companies listed on the Jakarta Stock Exchange (JSX) from 1997 to 2001, based on 8 non financial sectors. The sample technique is proportionate cluster random. The research type used is the verificative study by explanatory survey method.The data needed are cash flow statement that involves cash flow of operating, cash flow of investing, and cash flow of financing, closed stock prices per December 31 and stock returns. The data are collected from the Capital Market Reference Center, the Indonesian Capital Market Directory, and the Jakarta Stock Exchange Statistic. The data are analyzed by using multiple regression analysis, and hypothesis testing is done by using statistical test that involves F-test and t-test. The data are processed by using Statistical Program of Social Science (SPSS).The results of this research indicate: Simultaneously, the influence of cash flow statement that involves cash flow of operating, cash flow of investing, and cash flow of financing, to stock prices is 34.8%. Partially, the influence of cash flow statement to stock prices is as follows: cash flow of operating is 0.002909, cash flow of investing is -0.144, and cash flow of financing is -0.00446.  Simultaneously, there is no influence of cash flow statement to stock returns. It is indicated by ttest < ttable and R2 = 0.5%. Partially, also, there is no influence of cash flow statement to stock returns, indicated by ttest < ttable, and regression coefficients for each variable are very low, that is, cash flow of operating is -0.000000146, cash flow of investing is 0.0000000613, and cash flow of financing is -0.0000000449.